Teknik Penyeduhan dengan Metode Syphon, Moka Pot dan French Press - Egi Gustaman; Anna Anggraini (JURAGAN - Jurnal Agroteknologi, 2024)
Coffee is an agricultural commodity that is in great demand by the public. Coffee is a plant that belongs to the Rubiaceae family. The chemical composition is also influenced by the type of coffee, growing environment, and processing process. In Indonesia, robusta coffee (Coffea canephora) is widely cultivated. In this practicum, the parameters analyzed are organoleptic tests in the form of color, aroma, taste, clarity and after test using 3 types of brewing equipment, namely Shipon, French press and Moka-pot. The benefit of doing this practicum is that you can find out the organoleptic tests on the differences between brewing coffee A and coffee B using a siphon, French press and moka pot.